NGHIÊN CỨU CHẾ TẠO KEO DÁN TRÊN CƠ SỞ HỖN HỢP CAO SU NITRIL VÀ CAO SU THIÊN NHIÊN - Phan, Văn Trường; Đàm, Quang Sang; Nguyễn, Văn Bộ; Nguyễn, Văn Thành; Đỗ, Minh Hiếu (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH FOR PRODUCTION OF ADHESIVE ON THE BASE OF NITRILE RUBBER AND NATURAL RUBBER COMBINATIONAdhesives based on nitrile rubber are widely used in many different fields. In this article, the authors have proposed an application and process for making colloidal solutions based on a mixture of nitrile rubber and natural rubber. Research has been conducted to investigate the influence of the ratio of rubber components, the proportion of ingredients of fillers, the ratio of phenolformaldehyde resin to the calculation of technical requirements and the bond strength of the adhesive. Test results determine the bond strength is equivalent to BK-3 adhesive (in imported from Russia, OCT 1 190281-86).